PERANAN HABIB ABDURRAHMAN EL ZAHIR PADA MASA PEMERINTAHAN SULTAN IBRAHIM MANSYURSYAH DI KERAJAAN ACEH DARUSSALAM TAHUN 1864-1878 - Kholifa Tulhassana; Isjoni Isjoni; Ridwan Melay (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: As an empire, Aceh experienced a period of forward and backward. This also made the Royal Commander think of appointing and inaugurating a Sultan, who later the Sultan could restore the glory of the Kingdom of Aceh. That is why a Sultan named Sultan Ibrahim Mansyur Syah was appointed in his government assisted by Habib Abdurrahman El Zahir. The purpose of this study is 1) To find out who Habib Abdurrahman El Zahir was, 2) To find out about the condition of Aceh before the arrival of Habib Abdurrahman El Zahir, 3) To find out the role of Habib Abdurrahman El Zahir during the reign of Sultan Ibrahim Mansyursyah, 4) To find out how the end the presence of Habib Abdurrahman El Zahir in the Kingdom of Aceh Darussalam 1864-1878. In this study the author uses qualitative research methods with descriptive and historical approaches. This method is a research conducted by interpreting the data in the past or the present by using words on the results of the study. The results of this study are the emergence of Habib Abdurrahman El Zahir in Aceh around 1864, where the Aceh Sultanate was a meaningless government. Habib Abdurrahman El Zahir is a foreign figure of Arab descent who gained an important position in the kingdom of Aceh Darussalam in maintaining the glory and power of Aceh Darussalam. Habib obtained several important positions including being the Imam of the Grand Mosque, resolving internal conflicts, the delegation of diplomacy abroad, and negotiator with the Netherlands.Keywords: Role, Habib, Kingdom of Aceh Darussalam